1997
DOI: 10.1101/gr.7.9.897
|View full text |Cite
|
Sign up to set email alerts
|

A Radiation Hybrid Map of Human Chromosome 5 with Integration of Cytogenetic, Genetic, and Transcript Maps

Abstract: One of the major goals of the human genome project is to establish a physical map of each human chromosome with a density of sequence-tagged site (STS) markers exceeding one every 100 kb. We report here the generation of a human chromosome 5-specific radiation hybrid (RH) map that includes 556 markers. Of these markers, 132 loci are ordered with a maximum likelihood ratio of >1000:1 compared with the next most likely order. An additional 113 loci were ordered relative to these backbone markers with a maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…We have identified a novel target of miR200a, AP-2γ, a member of the developmentally regulated AP-2 transcription factor family that was originally identified from a MCF-7 cDNA library (McPherson et al, 1997). It is an important regulator of embryogenesis and tumor regenesis (Pellikainen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have identified a novel target of miR200a, AP-2γ, a member of the developmentally regulated AP-2 transcription factor family that was originally identified from a MCF-7 cDNA library (McPherson et al, 1997). It is an important regulator of embryogenesis and tumor regenesis (Pellikainen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…To date, five members of the AP-2 family have been identified: AP-2α, AP-2β, AP-2γ, AP-2δ and AP-2ε (Eckert et al, 2005). To date, little is known on the interaction between AP-2 transcription factors and miR-200 family; AP-2γ is a member of the developmentally regulated AP-2 transcription factor family that was originally identified from a MCF-7 cDNA library (McPherson et al, 1997). It is an important regulator of embryogenesis and tumor regenesis (Pellikainen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Human and mouse maps, based on information from Lahn and Page (1997) and Mazeyrat et al (1998), are meant to be proportionate to intergenic spacing, yet they do not necessarily reflect true physical distances. McPherson et al 1997;Schmitt et al 1996) RH panels. Stewart et al (1997) observed the centiray-tokilobase ratio to be roughly half on the Y chromosome, likely because of the increased breakage frequency of the Y.…”
Section: Comparative Mapping Of Y Chromosome Homologsmentioning
confidence: 99%
“…A direct comparison with radiation hybrid maps of 5p is also possible by use of markers shared by both studies (McPherson et al 1997). Whereas the experimentally determined linear order of markers is, in general, the same between the two maps, the number of markers on the physical map (Fig.…”
Section: Comparison With the Genetic And Radiation Hybrid Mapsmentioning
confidence: 99%
“…2) is nearly an order of magnitude greater. Like the genetic map, there is a greater than fivefold (14.8-81.5 cR/Mb observed, McPherson et al 1997) difference in the ratio of cR/Mb between various mapped markers, making direct comparisons imprecise. In the few cases in which radiation hybrid mapping could split markers that physical mapping could not (i.e., 675,405,5pC; 502,648 5pI; 663,426 5pM), this information did not assist in the unambiguous definition of the STS order.…”
Section: Comparison With the Genetic And Radiation Hybrid Mapsmentioning
confidence: 99%